The Early Neolithic settlement of Carrascal (Oeiras, Portugal) - Cardoso, João Luis (2024)
The Early Neolithic site of Carrascal is located on a soft slope of the valley of Barcarena (municipality of Oeiras, district of Lisbon), about 3 km from the northern margin of the Tagus estuary, and in the vicinity of a paleo-estuary located downhill and supplying an abundant collector activity, namely of oysters (Ostrea edulis). The abundance of cores and flakes recovered and the occurrence of silex in the cretaceous recifal limestones that exist around the site, is compatible with the inference of an important workshop; likewise, the production of polished stone artefacts made essentially with rocks of local origin has been proven; and, in the register of ceramic productions, with decorations typical of the Early Neolithic – incised and printed – large vessels occur, for the storage of various products, such as cereals. In effect, a manual millstone was collected, still in its original position. The faunal remains are rich and diversified, with the following taxa present: Bos primigenius; Bos taurus; Sus sp. and Ovis aries, showing the abundance of domestic animals as well as wild game. Finally, domestic structures are represented essentially by two cuvettes, excavated in the geological substrate, filled with basalt blocks collected in the vicinity, corresponding to fireplaces. Together, the abundance and diversity of the remains found indicates a perennial establishment corresponding to an important occupation dating to the last quarter of the 6th millennium BC, according to the six radiocarbon dates performed on faunal remains.